Technology transfer and the restructuring of new market economies: The case of Poland - Stanis±aw Kubielas (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1996)
The paper is an attempt to generalise some empirical evidence on the relationships between technology transfer and structural adjustment in the new market economies in Central and Eastern Europe. The Polish experience in 1989-1995 is selected as a point of reference. It is argued that ten stylised facts concerning the initial conditions of transformation for new market economies are decisive, if FDI is to become the most important channel of technology transfer. The model of structural adjustment by G Dosi, K Pavitt and L Soete, and the model of investment development path developed by M Porter and J Dunning, are merged to obtain a theoretical insight into the relationship between FDI-based technology transfer and economic restructuring. Implications for policy considerations are developed with regard to three types of structural adjustment: Ricardian, Keynesian and Schumpeterian. The analysis of data on FDI inlow into Poland in 1989-1995 shows a clear distinction between two periods - 1989-1991 and 1992-1995 - which fit well into two adjustment models, respectively Ricardian and Keynesian. The point is supported by evidence on FDI policy measures, FDI modes of investment, and strategies and performance of FDI-based firms. There are suggestive changes on all these indicators around 1992. A comparison of sectoral patterns of FDI with changes in patterns of revealed comparative advantage provides further support for the hypothesis that a switch from Ricardian to Keynesian adjustment processes occurred at that time. This comparison also gives us an indirect insight into the characteristics of technology transfer embodied in FDI. Finally, the prospect for Schumpeterian adjustment is explored.
Keywords: 330; Technologietransfer; Wirtschaftliche Anpassung; Auslandsinvestition; Multinationales Unternehmen; Polen